Holistic Approach of Swiss Fetal Progenitor Cell Banking: Optimizing Safe and Sustainable Substrates for Regenerative Medicine and Biotechnology - Laurent, Alexis; Hirt-Burri, Nathalie; Scaletta, Corinne; Michetti, Murielle; de Buys Roessingh, Anthony S.; Raffoul, Wassim; Applegate, Lee Ann (Frontiers in Bioengineering and Biotechnology, 2020)
Safety, quality, and regulatory-driven iterative optimization of therapeutic cell source selection has constituted the core developmental bedrock for primary fetal progenitor cell (FPC) therapy in Switzerland throughout three decades. Customized Fetal Transplantation Programs were pragmatically devised as straightforward workflows for tissue procurement, traceability maximization, safety, consistency, and robustness of cultured progeny cellular materials. Whole-cell bioprocessing standardization has provided plethoric insights into the adequate conjugation of modern biotechnological advances with current restraining legislative, ethical, and regulatory frameworks. Pioneer translational advances in cutaneous and musculoskeletal regenerative medicine continuously demonstrate the therapeutic potential of FPCs. Extensive technical and clinical hindsight was gathered by managing pediatric burns and geriatric ulcers in Switzerland. Concomitant industrial transposition of dermal FPC banking, following good manufacturing practices, demonstrated the extensive potential of their therapeutic value. Furthermore, in extenso, exponential revalorization of Swiss FPC technology may be achieved via the renewal of integrative model frameworks. Consideration of both longitudinal and transversal aspects of simultaneous fetal tissue differential processing allows for a better understanding of the quasi-infinite expansion potential within multi-tiered primary FPC banking. Multiple fetal tissues (e.g., skin, cartilage, tendon, muscle, bone, lung) may be simultaneously harvested and processed for adherent cell cultures, establishing a unique model for sustainable therapeutic cellular material supply chains. Here, we integrated fundamental, preclinical, clinical, and industrial developments embodying the scientific advances supported by Swiss FPC banking and we focused on advances made to date for FPCs that may be derived from a single organ donation. A renewed model of single organ donation bioprocessing is proposed, achieving sustained standards and potential production of billions of affordable and efficient therapeutic doses. Thereby, the aim is to validate the core therapeutic value proposition, to increase awareness and use of standardized protocols for translational regenerative medicine, potentially impacting millions of patients suffering from cutaneous and musculoskeletal diseases. Alternative applications of FPC banking include biopharmaceutical therapeutic product manufacturing, thereby indirectly and synergistically enhancing the power of modern therapeutic armamentariums. It is hypothesized that a single qualifying fetal organ donation is sufficient to sustain decades of scientific, medical, and industrial developments, as technological optimization and standardization enable high efficiency.